Transitioning from child to adult cleft lip and palate services in the United Kingdom: are the NICE Guidelines reflected in young adults’ experiences? - Mcwilliams, D; Thornton, M; Hotton, M; Swan, MC; Stock, NM (Taylor & Francis, 2022)
Cleft lip and/or palate (CL/P) is one of the most common congenital conditions worldwide. Individuals born with CL/P will embark on a long-term treatment pathway throughout childhood and often into adulthood. As they grow older, young people become more involved in medical decisions. The National Institute for Clinical Excellence (NICE) has published guidance for health professionals on how transitions of responsibility should be managed in health services. The aim of the current study was to examine the extent to which the NICE recommendations are currently being implemented in UK CL/P services according to young adults’ first-hand accounts. Semi-structured interviews were carried out with 15 young adults with CL/P aged 16-25 years. Interview questions were designed to map onto the NICE guidance. Data were analysed to assess whether each guideline was met, partially met, or not met for each individual participant. Overall, findings suggest that further consideration is needed as to how best to implement the recommendations effectively. The introduction of assigned transition workers in CL/P services to co-ordinate transition to adult care offers one possible solution. Focusing on the provision of holistic, patient-centred care, this aspect of the CL/P service could include giving patients access to medical history documentation, liaison with key health professionals including GPs and dental practitioners, and the development of age-appropriate resources to facilitate the transition process.